Inappropriate polypharmacy during the COVID-19 pandemic: impact, challenges, and solutions – a narrative review - Evelina Gavazova; Radiana Staynova; Daniela Grekova-Kafalova (Folia Medica)
The COVID-19 pandemic has brought unprecedented challenges to healthcare systems worldwide, impacting various aspects of patient care. Polypharmacy, the concurrent use of multiple medications by a single patient, is a significant concern exacerbated by the pandemic. The dual threat of COVID-19 infection and polypharmacy for the same vulnerable group – the elderly and those with pre-existing multimorbidity – is particularly problematic, as polypharmacy has been shown to lead to suboptimal treatment outcomes in many chronic diseases. This comprehensive review explores the multifaceted issues surrounding polypharmacy during the COVID-19 pandemic, addressing its causes, consequences, and potential solutions.